Review of Norbanus Walker (Hymenoptera: Pteromalidae) in Iran with the description of four new species - Rahmani, Zahra; Rakhshani, Ehsan; Lotfalizdaeh, Hossein; Mokhtari, Azizollah; Mitroiu, Mircea-Dan (Zootaxa, 2025)
The Iranian species of Norbanus Walker (Hymenoptera: Pteromalidae), are reviewed. Four new species, Norbanus brachymarginalis Rahmani & Rakhshani sp. nov., Norbanus brevispiculus Rahmani & Rakhshani sp. nov., Norbanus densipilosus Rahmani & Rakhshani sp. nov., and Norbanus flavitibialis Rahmani & Rakhshani sp. nov. are described from various regions in eastern (Sistan-o Baluchestan and North Khorasan), southeastern (Kerman), and western (Kermanshah) provinces of Iran. A key to the 14 Iranian and Iraqi species of Norbanus based on females is given.